Teachers’ Challenges in Teaching English in a Non Public School - Nuraini Nuraini (Institute of Information Technology and Social Science (IITSS), 2021)
The purpose of the research was to investigate the English teachers’ challenges in teaching at madrasah tsanawiyah. It also aimed to find out what kinds of effort that English teachers do in anticipating the challenges that they faced while teaching English as a foreign language. There were three English teachers are involved as the participant in this research. They come from of public-school Madrasah Tsanawiyah Jambi Timur and privat school Madrasah Tsanawiyah Dharma Wanita. In order to gain the necessary of the data in aswering the research questions, the data would be obtained by giving demographic questionnaire and doing in depth interview. The result indicates the main challenges factor that English teachers faced in teaching in this research are academic factors (students’ demotivation and low students’ basic English ability) and non-academic factors (lack of facilities, crowded classroom, socio economic level and school management). In the interview result indicate two unchallenges factors in term of academic factor (students’ attitude) and non-academic factor (curriculum). From the findings, the researcher could conclude that all the participants faced some challenges in teaching English with the difference factors. The challenges that the participants had can not be generalized because each participants have their own perspective to see something as a challenge or not.